Analysis of Bilingual Flash Card Learning Media to Improve Vocabulary Skills in Two Language Learning - Handayani, Nova Dwi; Widagdo, Arif; Noviana, Widia Kumara; Nikmah, Jazilatun; Zahro, Devi Fathimatuz; Sonia, Rada Ratu; Kinanthi, Mazaya Deaswara (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study seeks to examine the development of efficient bilingual flash card learning tools to enhance students' vocabulary abilities within bilingual education. The method employed in this research is a literature review utilizing a qualitative approach, examining multiple pertinent literature sources concerning the use of flash cards for language acquisition. The findings indicated that employing bilingual flash card media greatly enhanced students' vocabulary skills, showing an average improvement of up to 44% over traditional learning approaches. Bilingual flash card media facilitates students to compare and understand the differences and similarities between the two languages, thereby accelerating the process of vocabulary mastery simultaneously. The advantages of flash cards that are practical, efficient, easy to remember, and entertaining make them an appropriate choice for bilingual learning. Its implementation in the form of games also increases active participation, learning motivation, and student engagement in learning. Effective design pays attention to attractive visual aspects, contextual content, and interactive usage methods. This research concludes that bilingual flash card media is an effective solution to overcome the challenges of vocabulary mastery in bilingual learning, as well as contributing to the development of learning models that enrich students' learning experiences in a bilingual context.